PENGARUH MODEL LAPS-HEURISTIK TERHADAP KEMAMPUAN PEMECAHAN MASALAH DAN KEMAMPUAN BERPIKIR REFLEKTIF - Siti Nur Aida; Anggoro, Bambang Sri; Dewi, Novian Riskiana (Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2023)
The aim of this research is to determine whether there are differences in problem solving abilities and reflective thinking abilities between students who use the LAPS-Heuristic learning model and conventional learning. This type of research is quasi-experimental. The research was conducted at SMPN 5 Natar with a population of students from 6 classess VIII and a sample of 2 classes selected using a cluster random sampling technique. The hypothesis was tested with MANOVA test using SPSS 25 by first carrying out analysis prerequisite tests including normality tests and homogeneity tests. The results of the MANOVA analysis show that there are differences in problem solving abilities and reflective thinking abilities between students who use the LAPS-Heuristic learning model and conventional learning. These results can be used as material for further learning development using the LAPS-Heuristic model.